Perioperative tislelizumab with four cycles of neoadjuvant chemotherapy for resectable locally advanced esophageal squamous cell carcinoma: a phase 2 study - Zhou, Na; Hua, Yuwei; Ge, Yuping; Wang, Qiang; Wang, Chenyu; He, Jia; Zhao, Luo; Yu, Shuangni; Yan, Junfang; Zhao, Lin; Li, Li; Bai, Chunmei (Frontiers in Immunology, 2024)
BackgroundThe application of neoadjuvant immunotherapy in the treatment of esophageal cancer needs further exploration. This study aimed to investigate the safety and effectiveness of tislelizumab, an anti-PD-1 antibody, combined with chemotherapy as neoadjuvant treatment for locally advanced esophageal squamous cell carcinoma (LA-ESCC).MethodsIn this phase II study, patients with clinical stages of II-IVA (T3-T4 and/or node positive) potentially resectable LA-ESCC were enrolled. Patients received neoadjuvant tislelizumab and chemotherapy every 3 weeks for 4 cycles before surgery and adjuvant tislelizumab for 9 months. The primary endpoint was pathological complete response (pCR) rate. Secondary endpoints included R0 resection, disease free survival (DFS), adverse events (AE), and biomarkers for predicting efficacy.ResultsThe study included 30 patients. 25 patients completed neoadjuvant chemoimmunotherapy and underwent surgery, 96% with R0 resection. The pCR and MPR rate was 44% and 52%. The 6-month and 1-year DFS rate was 100% and 75.3%. 43.3% patients experienced severe (grade 3-4) treatment-related adverse events (TRAEs) and 5 patients developed severe immune-related adverse events (irAEs). Further exploration found that a group of peripheral lymphocyte subsets increased significantly after 2 cycles of neoadjuvant therapy in patients who achieved pCR, suggesting the importance of dynamic monitoring of circulating lymphocyte.ConclusionsThe combination of perioperative tislelizumab and neoadjuvant chemotherapy has achieved an encouraging pCR rate and demonstrated a manageable safety profile in patients with potentially resectable ESCC.Clinical Trial Registrationhttps://www.chictr.org.cn/, identifier ChiCTR2100043772.